The Transition of Aboriginal and Torres Strait Islander Students into Higher Education. - Oliver, Rhonda; Rochecouste, Judith; Grote, Ellen (Office for Learning and Teaching, 2013)
This project represents collaboration between four universities: Curtin University (lead), Monash University, The University of New England and Charles Darwin University. The project team investigated processes involved in transitioning Indigenous students to higher education across all Australian university Aboriginal centres. Several qualitative data collection methods were employed: initial interviews and focus groups at the participating universities formed an extensive survey. the findings were available for distribution across all university Aboriginal centres. Particular attention will be given to inclusive data analysis procedures to identify success and best practice in this area. Resultant deliverables included an online resource providing advice for policy and practice on best practice in the transition of minority Indigenous groups to higher education. This resource is also available in print form. It is also envisaged that the project's strategy for internal communication and inclusive engagement will provide a model for future collaborative studies of this kind.